2019
DOI: 10.1002/anie.201907464
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Poly(tert‐butyl acrylate) Photonic Crystals towards Robust Energy‐Saving Performance

Abstract: Photonic crystals (PCs) have been widely applied in optical, energy,a nd biological fields owingt ot heir periodic crystal structure.H owever,t he major challenges are easy cracking and poor structural color,s eriously hindering their practical applications.Now,hydrophobic poly(tert-butyl acrylate) (P(t-BA)) PCs have been developed with relatively lower glass transition temperature (T g ), large crack-free area, excellent hydrophobic properties,a nd brilliant structure color. This method based on hydrophobic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 64 publications
0
92
0
Order By: Relevance
“…More recently, an alternative microfluidic spinning technology (MST) is emerged to provide an ideal strategy for facile fabrication of aligned microfibers. [35][36][37][38][39][40] In addition, more complicated and interesting structures, including string-of-beads [41] and Janus fibers, [42][43] can be easily manipulated by adjusting the geometric features of the microfluidic channels. For example, Kong et al reported spindle-knot microfibers with cavity knots for large-scale water collection by a gas-in-water microfluidic system.…”
Section: Robust Nanofiber Films Prepared By Electro-microfluidic Spinmentioning
confidence: 99%
“…More recently, an alternative microfluidic spinning technology (MST) is emerged to provide an ideal strategy for facile fabrication of aligned microfibers. [35][36][37][38][39][40] In addition, more complicated and interesting structures, including string-of-beads [41] and Janus fibers, [42][43] can be easily manipulated by adjusting the geometric features of the microfluidic channels. For example, Kong et al reported spindle-knot microfibers with cavity knots for large-scale water collection by a gas-in-water microfluidic system.…”
Section: Robust Nanofiber Films Prepared By Electro-microfluidic Spinmentioning
confidence: 99%
“…After uniform mixing, the coating ink was casted onto ap olyethylene terephthalate (PET) film and spread by a90mm-depth spiral bar. [17] After water evaporation, al arge-scale fluorescent CDs/PVAf ilm (50 40 cm) could be obtained. Figure 3d shows photographs of three color-converting films with blue (Zn-CDs,d 1), green (Na-CDs,d 2), and yellow (K-CDs,d 3) emissions under UV light, which exhibit bright and uniform fluorescence colors.W ea lso measured the Commission Internationable de LEclairage (CIE) chromaticity values, as shown in Figure 3e.T he CIE coordinates were located at (0.18, 0.16), (0.27, 0.41), and (0.40, 0.48) for blue,g reen, and yellow fluorescent films,respectively,which is in line with the fluorescent colors of CDs in water solvent.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The bandgap derived from highly ordered periodic structures is responsible for uniformly reflected colours in the visible spectrum. Accordingly, a variety of techniques, like photolithography [ 4 ], screen printing [ 5 ], atomisation deposition [ 6 ], inkjet printing [ 7 , 8 ], spray coating [ 9 , 10 ], gravity sedimentation [ 11 , 12 ], and electrophoretic deposition [ 13 , 14 ], have been proposed for the adhibition by applying photonic crystals onto substrates in several applications, including paints and inks [ 5 ], smart windows [ 3 ], energy-saving devices [ 15 ], night-time traffic safety and advertisement display [ 16 ], anti-counterfeiting security [ 4 , 17 , 18 ], eyeglasses and photographic lenses [ 19 ], and information storage [ 20 ]. To realise such promising industrial applications, the studies on the large-area scalable fabrication technique of photonic crystals have been conducted, including melt-shear organization method [ 21 ] and oscillatory shear technique [ 22 ].…”
Section: Introductionmentioning
confidence: 99%